Clinical syndromes: Parkinsonian gait. Issue 11 (16th October 2013) - Ebersbach, Georg; Moreau, Caroline; Gandor, Florin; Defebvre, Luc; Devos, David
ABSTRACT Disturbances of gait manifest in almost all cases of Parkinson's disease (PD), often leading to loss of mobility and increased mortality. In this review a clinically oriented approach to gait disorders in different stages of PD is presented. In addition, interactions between motor behavior and mental processing will be discussed. Analyzing the clinical features of gait can be helpful to differentiate PD from atypical forms of parkinsonism. Bedside tests to distinguish parkinsonian gait disorders are reviewed. There is still an unmet need to effectively treat complex gait disturbances, which are frequently not responsive to dopamine replacement medication. We thus present current approaches for the management of dopa‐refractory gait disorders. © 2013 International Parkinson and Movement Disorder Society